Resource loss and mental health during COVID‐19: Psychosocial protective factors among U.S. older adults and those with chronic disease. (16th August 2021) - McElroy‐Heltzel, Stacey E.; Shannonhouse, Laura R.; Davis, Edward B.; Lemke, Austin W.; Mize, Mary Chase; Aten, Jamie; Fullen, Matthew C.; Hook, Joshua N.; Van Tongeren, Daryl R.; Davis, Don E.; Miskis, Constantinos
Abstract : Across the globe, COVID‐19 has disproportionately affected the physical and mental health of several vulnerable groups. In a series of two cross‐sectional studies conducted April to July 2020, we examined its acute mental health effects on two vulnerable U.S. community samples—home‐bound older adults who were at or below the poverty line (Study 1, N  = 293, M age  = 76.94, SD  = 8.64; 75.1% female, 67.9% Black) and adults with chronic disease (Study 2, N  = 322, M age  = 62.20, SD  = 12.22; 46.3% female, 28.3% racial/ethnic minorities). Based on the conservation of resources theory, we hypothesised that pandemic‐related resource loss would be associated with greater mental distress, but perceived social support and positive psychological characteristics (trait resilience and optimism) would buffer against this adverse effect. Across both samples of vulnerable adults, pandemic‐related resource loss was related to mental distress. Perceived social support was related to lower mental distress but did not consistently buffer the effect of resource loss on mental health. However, in Study 2, both trait resilience and optimism buffered this relationship. Findings are discussed in terms of their implications for the conservation of resources theory.